A new species of the genus Eurhadina Haupt (Hemiptera: Auchenorrhyncha: Cicadellidae: Typhlocybinae) from Korea, with a key to Korean species - Oh, Sumin; Lim, Jongok; Jung, Sunghoon (Zootaxa, 2016)
The leafhopper genus Eurhadina Haupt, 1929 belongs to the tribe Typhlocybini of subfamily Typhlocybinae (Hemiptera: Auchenorrhyncha: Cicadellidae). Currently, genus Eurhadina includes 3 subgenera, Eurhadina Haupt 1929, Singhardina Mahmood 1967, Zhihadina Yang & Li 1991. A total of 20 valid species of subgenus Eurhadina have been described in the Nearctic and Palaearctic region and the subgenus Singhardina includes 57 species in the Oriental and Palaearctic region (Huang & Zhang 1999, Dworakowska 2002). The subgenus Zhihadina includes only 1 species from China (Yang & Lee, 1991). So far, four species of subgenus Eurhadina were recorded in the Korean Peninsula (Kwon & Huh 2001): Eurhadina (Eurhadina) betularia Anufriev, 1969, E. (E.) koreana Dworakowska, 1971, E. (E.) pulchella (Fallen, 1806), and E. (E.) wagneri Dworakowska, 1969. The majority of species belonging to the subgenus Eurhadina are difficult to distinguish by external appearance because the color patterns of the forewings are very similar among species.